Are Works of Art Affective Artifacts? If Not, What Sort of Artifacts Are They? - Terrone, Enrico (Topoi: An International Review of Philosophy, 2024)
Works of art are usually meant to elicit psychological effects from their audiences whereas paradigmatic technical artifacts such as hammers or cars are rather meant to produce physical effects when used. This suggests that works of art and technical artifacts are sharply different entities. However, recent developments in the cognitive sciences and the philosophy of technology have individuated special artifacts, namely cognitive and affective artifacts, which also generate psychological effects. In particular, affective artifacts, which have the capacity to alter the affective condition of agents, seem to share crucial features with works of art. Can we subsume works of art under that kind? I will argue that we cannot. Still, comparing art with affective artifacts will help us to clarify the relationship between art and technology, and to introduce a new category, namely the experiential artifact, which can properly encompass works of art.